Evaluation and lessons learned from an undergraduate service learning course providing youth-focused relationship education. (October 2016) - McElwain, Alyssa; Finnegan, Vanessa; Whittaker, Angela; Kerpelman, Jennifer; Adler-Baeder, Francesca; Duke, Adrienne
Highlights: Service learning facilitates a connection between undergraduates and community needs. Undergraduate student are effective facilitators of youth relationship education. Adolescent participants experienced change in individual and relational variables. Lessons learned relate to partnerships, training, and program participants. Abstract: Adolescent romantic relationships are known to have a significant impact on individual well-being and development. However, few teens experience formal education about the knowledge and skills necessary for building healthy romantic relationships. In response, a statewide relationship education initiative was developed at a large university in a Southeastern state. Undergraduates who enrolled in a service learning course in Human Development and Family Studies partnered with this initiative and implemented a relationship education program targeting high school students. A service learning model is used in this initiative because it offers opportunities for students' professional development and experiential learning. The present article provides a formative and illustrative summative evaluation of the service learning program. Specifically, the primary aims of this paper are to 1) provide an overview of the service learning course components; 2) describe preparation of the service learning students and their implementation of the relationship education program; 3) discuss challenges and lessons learned; and 4) offer initial evidence of effectiveness by showing change in targeted outcomes for the high school student recipients of the relationship education program.